Effect of exogenous selenium supply on photosynthesis, Na+ accumulation and antioxidative capacity of maize (Zea mays L.) under salinity stress - Jiang, Chaoqiang; Zu, Chaolong; Lu, Dianjun; Zheng, Qingsong; Shen, Jia; Wang, Huoyan; Li, Decheng (Scientific reports, 2017)
The mechanism of selenium-mediated salt tolerance has not been fully clarified. This study investigated the possible role of selenium (Se) in regulating maize salt tolerance. A pot experiment was conducted to investigate the role of Se (0, 1, 5 and 25 μM Na 2 SeO 3 ) in photosynthesis, antioxidative capacity and ion homeostasis in maize under salinity. The results showed that Se (1 μM) relieved the salt-induced inhibitory effects on the plant growth and development of 15-day-old maize plants. Se application (1 μM) also increased the net photosynthetic rate and alleviated the damage to chloroplast ultrastructure induced by NaCl. The superoxide dismutase (SOD) and ascorbate peroxidase (APX) activities were increased, and ZmMPK5, ZmMPK7 and ZmCPK11 were markedly up-regulated in the roots of Se-treated plants, likely contributing to the improvement of antioxidant defence systems under salinity. Moreover, 1 μM Se increased K + in the shoots while decreasing Na + in the roots, indicating that Se up-regulates ZmNHX1 in the roots, which may be involved in Na + compartmentalisation under salinity. The findings from this single experiment require repetition together with measurement of reactive oxygen species (ROS), but nevertheless suggest that exogenous Se alleviates salt stress in maize via the improvement of photosynthetic capacity, the activities of antioxidant enzymes and the regulation of Na + homeostasis.